2006
DOI: 10.1007/s10592-005-9099-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of partial anadromy and resident-form dispersal bias on a fine scale in populations of Oncorhynchus mykiss

Abstract: We examine sympatric anadromous (steelhead) and nonanadromous (resident) rainbow trout (Oncorhynchus mykiss) from neighboring locations to test three hypotheses: (1) the sympatric life history types are not genetically different; (2) fine-scale dispersal is the same for both sexes, and (3) fine-scale dispersal is the same for steelhead and resident individuals. Data from 13 microsatellite loci reveal no genetic difference between sympatric steelhead and resident O. mykiss but moderate population structure (F S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 28 publications
(27 reference statements)
3
53
1
Order By: Relevance
“…This pattern is consistent with previous studies of coastal steelhead, which found similar signals of IBD Garza et al 2014). A similar pattern of structuring by geography and not phenotype has also been observed in other anadromous and resident O.mykiss populations (Docker et al 2003;Olsen et al 2006;Pearse et al 2007;Clemento et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…This pattern is consistent with previous studies of coastal steelhead, which found similar signals of IBD Garza et al 2014). A similar pattern of structuring by geography and not phenotype has also been observed in other anadromous and resident O.mykiss populations (Docker et al 2003;Olsen et al 2006;Pearse et al 2007;Clemento et al 2009). …”
Section: Discussionsupporting
confidence: 91%
“…Interchange between forms was also observed in the Santa Cruz River, Argentina, where steelhead apparently evolved from resident trout (Pascual et al 2001;Riva-Rossi et al 2007). Perhaps not surprisingly, molecular analysis has seldom revealed genetic divergence between anadromous and resident individuals where fish displaying these life histories patterns are sympatric (Docker and Heath 2003;McPhee et al 2007;Olsen et al 2006), consistent with evidence for considerable interbreeding between life histories from parentage analysis (Christie et al 2011;Seamons et al 2004) and direct observation (McMillan et al 2007). …”
Section: Oregon; Sloat and Reeves 2014mentioning
confidence: 76%
“…The degree of genetic differentiation between resident and anadromous populations of O. mykiss in sympatry is variable. Most studies examining genetic differentiation between sympatric life-history types of O. mykiss reveal that alternative lifehistory forms within the same freshwater system are more closely related to one another than are the same life-history types across river systems (Docker and Heath 2003;Narum et al 2004;Olsen et al 2006;McPhee et al 2007); however, there are some instances where significant reproductive isolation has been observed between sympatric O. mykiss life-history forms (Docker and Heath 2003;Narum et al 2004). In other words, resident and anadromous O. mykiss in sympatry exhibit some level of gene flow, and there is evidence for plasticity in the expression of the alternative life histories.…”
Section: Resultsmentioning
confidence: 99%